Non-Newtonian Natural Convection Flow along a Horizontal Circular Cylinder with Uniform Surface Heat Flux. (16th July 2013) - Bhowmick, Sidhartha; Molla, Md. Mamun; Hossain, Md. Anwar
Abstract : Laminar two-dimensional natural convection boundary-layer flow of non-Newtonian fluids along a horizontal circular cylinder with uniform surface heat flux has been studied using a modified power-law viscosity model. In this model, there are no unrealistic limits of zero or infinite viscosity; consequently, no irremovable singularities are introduced into boundary-layer formulation for such fluids. Therefore, the boundary-layer equations can be solved numerically by using marching order implicit finite difference method with double sweep technique. Numerical results are presented for the case of shear thinning as well as shear thickening fluids in terms of the fluid velocity and temperature distributions, shear stresses, and rate of heat transfer in terms of the local skin friction coefficient and local Nusselt number, respectively.